Proses Sosialisasi Antara Ani-Ani dan Mbuk Dalam Komunitas Waria di Palembang: Perspektif Interaksionisme Simbolik - Ira Hairida Yuliani; Dadang Hikmah Purnama; Yus naini (Jurnal Empirika, 2016)
The research aims to observe the exchange of experience between the  young transgender and the transgender community. This is a qualitative research which adopts the ethnographic approach. Qualitative data were extracted from primary source;  obtained  using  participative  field  observations,  interviews  and  focus group discussions. The data were analyzed using Spradley’s taxonomic analysis. The field observations were conducted in the beauty salons and red light zones. The researcher interviewed the informants, ‘ani-ani’ (the young transgenders) and ‘mbuk‟ (senior transgenders) and conducted the focus group discussions with senior transgenders.The result shows that the socialization process between ani- ani and mbuk is an anticipatory socialization process where the ani-ani comes into the transgender community voluntarily. This thesis also discovers that the socialization process is not a one-way process, on the contrary it is a dynamic process in which the self adjust the information they receive with their own values and needs. In the socialization process, each individual would adjust themselves with transgender community, thus although each experienced the same socialization process, the result of self-concept would be differ from one another.